Thinking through Art, Creating through Text - Milech, Barbara; Schilo, Ann (Sense Publishers, 2013)
Seventeen years ago, I was thrown in at the deep end of supervision. I had just completed my own PhD, the first staff member in my School of Art to hold one, and so deemed qualified to supervise our School’s first doctoral applicant.